1996
DOI: 10.1097/00005176-199610000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of 24-Hour Polyamine Intake From Mature Human Milk

Abstract: It has been suggested that milk polyamines stimulate GI tract proliferation and maturation in newborns. We determined human milk polyamine concentrations and estimated 24-h outputs on days 16 +/- 4 (n = 98), 44 +/- 3 (n = 97) and 91 +/- 6 (n = 25) after delivery. Median concentrations in micromolars were, respectively, putrescine 0.77, 0.63, and 0.63; spermidine 4.54, 3.07, and 2.73; spermine 3.76, 2.90, and 2.22; and total polyamines 9.82, 6.83, and 5.71. Concentrations of spermidine, spermine, and total poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 18 publications
5
26
0
2
Order By: Relevance
“…Several studies have been published evaluating the polyamine concentrations in human milk, but reported results were highly different because of the different methodologies; milk collection, storage and analysis; and high interindividual variability. All the previous studies support the conclusion that putrescine is less abundant in human milk comparing with spermidine and spermine, and our study agrees with earlier reports by Romain et al [5] , Dorhout et al [27] , and Atiya Ali et al [3] . Regarding spermidine and spermine in human milk, several reports show more heterogenic data.…”
Section: Milk Polyamines Compositionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several studies have been published evaluating the polyamine concentrations in human milk, but reported results were highly different because of the different methodologies; milk collection, storage and analysis; and high interindividual variability. All the previous studies support the conclusion that putrescine is less abundant in human milk comparing with spermidine and spermine, and our study agrees with earlier reports by Romain et al [5] , Dorhout et al [27] , and Atiya Ali et al [3] . Regarding spermidine and spermine in human milk, several reports show more heterogenic data.…”
Section: Milk Polyamines Compositionsupporting
confidence: 93%
“…Our results for spermidine were similar to those reported by Romain et al [5] , Dorhout et al [27] , and Atiya Ali et al [3] ; and higher than those reported by Buts et al [4] and Pollack et al [28] . For spermine, our results are similar to those reported by Romain et al [5] and higher than those reported by Buts et al [4] , Pollack et al [28] , Dorhout et al [27] , and Atiya Ali et al [3] . Therefore, common methodologies are required to assess and compare the concentrations of polyamines in human milk.…”
Section: Milk Polyamines Compositionsupporting
confidence: 92%
“…() and Dorhout et al . (), being 77 and 129 nmol dL −1 , respectively. This variation in putrescine levels may be a result of dietary variability and methodology, although genetic differences cannot be excluded (Romain et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, all mothers provided samples of hind milk. In another study that analysed breast milk with a relatively low fat content, indicating that it was not hind milk, the putrescine and spermidine concentrations were similar to those shown in the present study (Dorhout et al ., ). This might suggest that the polyamine concentration is not influenced by the emptying phase of the breast.…”
Section: Discussionmentioning
confidence: 99%